RELATIONSHIPS AMONG THE PASTURE STRUCTURE AND THE SELETIVITY OF EQUINE WHILE GRAZING - DITTRICH, João Ricardo (Scientia Agraria, 2002)
The grasses structure and grazing horses was investigated in two experiments at Canguiri farm (Parana Federal University). The first experiment proposed six differents Cynodon grasses with two kinds of patchs (tall and short) were distributed in a completely randomized design with four replications for each graminea. Five grazing tests were done with mares, evaluating the number of bites and bite depth allocated in each treatment. A preference for Tifton 85 was observed, followed by Coastcross-1. Tifton 68, Tifton 44, Estrela Roxa and Porto Rico were no preferred. Tall patches were preferred. In the second experiment the Cynodon sp. (Tifton 85), Paspalum paniculatum, Trifolium repens and Lotus corniculatus grasses were allocated in 4 randomized blocks, in strip with Cynodon or Paspalum and in mixture this grasses with the legumes. Four grazing tests were done with 3 horses in each block, evaluating the grazing site in each treatment. The preference was evaluated through largest stay time between the treatments and marked tillers. Mixtures were preferred. Tifton 85 mixture were plus preferred that Paspalum. Among unmixed species the preference is the following: Tifton 85, Paspalum paniculatum, Trifolium repens. Lotus corniculatus were no preferred. A linear relationship was found between tiller height and bite depth, demonstrate per y = 0,5196x + 1,4272 (r2 = 0,83).